2020
DOI: 10.1111/and.13816
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin treatment on the basal and gonadotropin‐stimulated steroidogenesis in male rats with type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus impairs reproductive functions in men, and important tasks are deciphering the mechanisms of testicular dysfunctions in diabetes and the search of effective approaches to their correction. The purpose was to study the effect of four‐week metformin treatment (120 mg kg−1 day−1) of male Wistar rats with high‐fat diet/low‐dose streptozotocin‐induced type 2 diabetes on basal and gonadotropin‐stimulated steroidogenesis, intratesticular content of leptin and the leptin and luteinising hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
(86 reference statements)
2
10
0
7
Order By: Relevance
“…Since MF improves metabolic and hormonal indices and testicular morphology in T2DM, there is reason to believe that the testicular response to LH/hCG-R-agonists, reduced in diabetic pathology, can increase with MF treatment. This is also supported by our data that MF improves the stimulation of testosterone production caused by a single injection of hCG [ 50 ]. However, the effect of MF therapy on the steroidogenic and spermatogenic effects of hCG, which is injected into diabetic animals for several days, has not yet been studied.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Since MF improves metabolic and hormonal indices and testicular morphology in T2DM, there is reason to believe that the testicular response to LH/hCG-R-agonists, reduced in diabetic pathology, can increase with MF treatment. This is also supported by our data that MF improves the stimulation of testosterone production caused by a single injection of hCG [ 50 ]. However, the effect of MF therapy on the steroidogenic and spermatogenic effects of hCG, which is injected into diabetic animals for several days, has not yet been studied.…”
Section: Introductionsupporting
confidence: 84%
“…Most studies carried out on experimental models of diabetes and obesity support a significant improving effect of MF on spermatogenesis and testicular steroidogenesis [ 7 , 19 , 50 , 70 , 78 , 100 , 101 , 102 , 103 , 104 ]. Moreover, both monotherapy with MF and its co-administration with pioglitazone [ 101 ] and natural antioxidants [ 78 , 105 , 106 ] were effective in the restoration of reproductive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have found that metformin can improve the testicular function and spermatogenesis of obese male mice induced by high-fat and high-cholesterol diet (22), and restore the gonadotropin and leptin systems in the testes of streptomycin-induced male rats (23). However, given the complex between glycemic control and hormone, these studies did not rule out the effect of blood glucose changes on it.…”
Section: Discussionmentioning
confidence: 98%
“…Metformin is an oral biguanide insulin-sensitizing drug used over the past 50 years to treat type 2 DM (103). In a few studies, treatment with metformin in diabetic male rats enhanced male reproductive parameters, such as serum and intratesticular testosterone levels, Leydig cell count, improved sperm quality parameters, and decreased sperm nuclear DNA fragmentation (104)(105)(106)(107)(108)(109). Furthermore, a study performed on oligo-terato-asthenozoospermic patients with MetS treated with metformin showed an increased serum androgen levels and consequently an enhancement of semen quality (110).…”
Section: Pharmacological Treatment Of Dm With Metformin and Its Implication On Sperm Quality And Art Outcomesmentioning
confidence: 99%
“…The mechanisms of action of metformin proposed in the testis and epididymis encompass the regulation of the expression of genes involved in steroidogenesis and hormone regulation. Diabetic rats treated with metformin showed an increase in the expressions of StAR, CYP11A1, CYP17A1, androgen receptor, LH receptor, and leptin receptor in comparison with obese nontreated animals (107,109). In addition, it was proposed that metformin can prevent testicular damage in diabetic mice by inhibiting apoptosis and inducing autophagy, through the PK2/PKR/AKT/GSK3b signaling pathway (111).…”
Section: Pharmacological Treatment Of Dm With Metformin and Its Implication On Sperm Quality And Art Outcomesmentioning
confidence: 99%